2017
DOI: 10.1093/femsle/fnx192
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence typing and virulence genotyping of Streptococcus suis serotype 9 isolates revealed high genetic and virulence diversity

Abstract: Streptococcus suis is an important swine pathogen that can cause a variety of diseases. Streptococcus suis serotype 9 (SS9) is a prevalent serotype, but limited information is available. Here, we studied and compared 30 SS9 isolates, including 24 isolates from China between year 2004 and 2013, 5 isolates from Vietnam and a serotype reference isolate from Denmark. A multilocus sequence typing (MLST) analysis was performed to exploit the genetic relationships between those isolates. The phylogenetic tree based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…It is important to note that this serotype is not considered highly prevalent in diseased pigs in this country [ 12 ]. Interestingly, similar high heterogeneity has been recently reported for serotype 9 strains isolated in Asia, where most strains belong to STs not previously described and also different from those herein observed [ 22 ]. Similar to Spanish and Canadian strains analyzed in the present study, no CC16 strain (with a higher zoonotic potential) was detected among Chinese strains [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is important to note that this serotype is not considered highly prevalent in diseased pigs in this country [ 12 ]. Interestingly, similar high heterogeneity has been recently reported for serotype 9 strains isolated in Asia, where most strains belong to STs not previously described and also different from those herein observed [ 22 ]. Similar to Spanish and Canadian strains analyzed in the present study, no CC16 strain (with a higher zoonotic potential) was detected among Chinese strains [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, different virulence factors have been proposed for this serotype and some of these are exclusively present among strains of a given geographical area [ 19 ]. On the other hand, few data are available for serotype 9 strains, despite the growing importance of this serotype as a swine pathogen; in fact, only a few studies have reported that not all serotype 9 strains have the same virulence potential [ 20 22 ], although it is generally accepted that strains of this serotype are less virulent than those of serotype 2 after experimental intranasal infections [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was notable that all isolates belonging to cps 9 were rather heterogenic harboring five different STs, although one abundant ST (ST1105, n = 8/14) seemed to be predominant among the identified samples. The genetic diversity of cps 9 isolates in China and Canada showed a high variety among examined isolates [ 47 , 48 ], which is comparable to the observed genetic diversity of inspected Swiss isolates. Interestingly, the aforementioned clone comprising ST1105 reoccurred within six different years (Figure 2 ) emphasizing its importance among the pig population in Switzerland and its ability to induce infections.…”
Section: Discussionsupporting
confidence: 52%
“…We found that virulence genotypes of these isolates were not in accordance with their virulence phenotypes, which was also observed in serotype 9 strains in our previous study (Dong et al., ). Genes sly and mrp were only detected in NCL25 strain WUSS328.…”
Section: Discussionsupporting
confidence: 47%
“…Although 11 of 13 virulence genes were detected in strain WUSS328, its virulence is lower than that of NCL26 strain NJ1112 in both zebrafish and mouse infection models. Similarly, serotype 9 strains NJ-4 and GD06896 without epf, sly and mrp genes even showed a higher level of virulence compared with serotype 2 virulent strain P1/7 in a mouse infection model (Dong et al, 2017). One possible reason is that most virulence studies of S. suis were conducted in serotype 2, so it may not be suitable to use these genes as genotypic markers for predicting virulence of non-serotype 2 strains (Dong et al, 2017).…”
Section: Multiplex Pcr Assaymentioning
confidence: 99%